Mechanism of blood-brain barrier disruption by an Escherichia coli from lambs with severe diarrhea and meningoencephalitis. (October 2020) - Wang, Weiyu; Cai, Menglu; Hu, Junying; Zhang, Zecai; Wang, Xu; Chang, Xiaoran; Zhang, Fan; Guo, Changming; Wang, Xinping
Abstract: Escherichia coli (E. coli) is a common conditional pathogen that is associated with a variety of infections in humans and animals. Although there are increasing reports regarding the infection of E. coli to domestic animals and poultry, the infection of E. coli in lambs is relatively less reported, especially on meningoencephalitis. Here, we reported the isolation of an E. coli strain designated as NMGCF-19 from lambs characterized with severe diarrhea and neurological disorder, and demonstrated that NMGCF-19 as the causative agent has the ability to disrupt the blood-brain barrier (BBB) to cause the meningoencephalitis using a mouse model. Investigation on the mechanism regarding the NMGCF-19-related meningoencephalitis revealed a significant decreased expression of ZO-1 and occludin in mouse brain tissue in comparison with the control mice. Moreover, infection of NMGCF-19 increased the expression of proinflammatory cytokines TNF-α, IL-6, IL-1β and IL-18, up-regulated HMGB1 level, and activated TLR2/TLR4/MyD88 and NLRP3 inflammasome pathways. These findings indicated that NMGCF-19 likely invades the brain tissue by disrupting the tight junction (TJ) architecture and causes the meningoencephalitis via increasing inflammatory response and activating TLR2/TLR4/MyD88 and NLRP3 inflammasome pathways. Highlights: E. coli isolate designated as NMGCF-19 caused lambs meningoencephalitis. A large number of NMGCF-19 were observed in the brain of lambs and mice. NMGCF-19 infection decreased TJ proteins expression in the brain of mice. NMGCF-19 infection promoted the inflammatory response in the brain of mice.